Comprehensive Analysis of Genetic Mutations and Inflammatory Markers Associated with Multiple Sclerosis in Iraqi Patients - Muataz Mohammed Al-Taee (American Journal of Biology and Natural Sciences, 2026)
Both hereditary and environmental factors contribute to multiple sclerosis (MS), a chronic autoimmune disease of the central nervous system marked by neural degeneration and myelin loss. This study aims to examine the relationship between the onset of MS and the vulnerability of Iraqi patients concerning inflammatory markers (TNF-α, IL-6, and IL-17) and genetic polymorphisms (HLA-DRB1, IL-7R, IL-2R). The study is conducted with 100 subjects recruited from renowned neurology clinics and hospitals in Iraq; 50 among them having a confirmed diagnosis of multiple sclerosis and the other 50 were age and sex matched healthy controls. Cytokine levels were quantified using enzyme-linked immunosorbent assay (ELISA), and genetic studies were performed using PCR and Sanger Sequencing. For identifying the immune system alterations whose mutations could be functional and causative, bioinformatics analysis was necessary to study the observed mutations. Results showed important genetic changes relative to high neuroinflammatory cytokines and greater predisposition to multiple sclerosis. The identification of new genetic associations and inflammatory markers which could potentially serve as therapeutic targets and diagnostic indicators increases precision medicine approaches for MS patients in Iraq and worldwide.